2019
DOI: 10.1155/2019/2318157
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Then Individual Separation of Platinum, Palladium, and Rhodium from Spent Car Catalytic Converters Using Hydrometallurgical Technique followed by Successive Precipitation Methods

Abstract: Recovery of PGMs (especially rhodium, platinum, and palladium) from different spent manufactured products (like catalytic converters) is considered as an important task as they are rarely found in nature, and they possess high economic value. In this work, the honeycomb of a car catalytic converter was primarily processed by crushing, grinding, and then treating in a hydrogen atmosphere. In order to establish an economic and ecofriendly method for the recovery of studied PGMs, different experimental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Another study reported spent automotive catalysts that were heated under a hydrogen atmosphere at 250 • C, which improved metal recovery during leaching due to the elimination of the hydrocarbons and charcoal present on the catalyst surface and the reduction of oxidized PGMs [38]. Pretreatment of the catalytic powder also assists in stabilizing the PGMs in their metallic form, making them easy to dissolve with leaching solutions [45].…”
Section: Preprocessingmentioning
confidence: 99%
“…Another study reported spent automotive catalysts that were heated under a hydrogen atmosphere at 250 • C, which improved metal recovery during leaching due to the elimination of the hydrocarbons and charcoal present on the catalyst surface and the reduction of oxidized PGMs [38]. Pretreatment of the catalytic powder also assists in stabilizing the PGMs in their metallic form, making them easy to dissolve with leaching solutions [45].…”
Section: Preprocessingmentioning
confidence: 99%
“…Some conditions have been reported to precipitate Pd ions from several kinds of aqueous solutions containing other ions. It has been found that addition of NaClO3 to the acidic solution in the absence of platinum ion could oxidize Pd(II) to Pd(IV) and slowly precipitate Pd(IV) as (NH4)2PdCl6 at high temperature (90°C) [9,10]. Besides, (NH4)2PdCl6 can be precipitated from the aqua regia solution containing Zn, Ni, Ag, Au by adding NH4Cl but the purity of the precipitates has not been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…Noble metals, such as platinum, palladium, rhodium, and gold, are some of the most valuable elements due to their exceptional properties, such as high chemical and thermal resistance, which directly leads to their wide applicability in the electrical, jewelry, and automotive industries [1][2][3][4]. Due to their scarcity in the deposits naturally occurring in the Earth s crust, the current manufacturing tendency is slowly shifting to obtaining them from secondary raw materials, e.g., automotive catalysts, computer parts, and other electronic equipment [5][6][7]. Recovering noble metals from such sources is not an easy task, due to the similarity of their properties and the presence of other metals such as copper, iron, and zinc, which often hinder the recovery process [8,9].…”
Section: Introductionmentioning
confidence: 99%